Dietary patterns in relation with nutritional outcomes and associated factors among adolescents: implications for context-specific dietary intervention for the Agrarian Community, Northwest Ethiopia - Agedew, Eskezyiaw; Abebe, Zeweter; Ayelign, Abebe (Frontiers in Nutrition, 2023)
Introduction: Dietary pattern analysis allows us to characterize the dietary intakes of individuals rather than nutrient intake data and strongly predicts disease risks. The relationship between food intake and adolescents' nutritional health is not well understood, yet. Objective: to determine dietary patterns and their relation to nutritional outcomes and to identify the contributing factors among adolescents. Methods: A cross-sectional survey was conducted among 622 randomly selected adolescents. Dietary data was collected over a one-week recall period using the Food Frequency Questionnaire (FFQ). Exploratory factor analysis was conducted to determine the dietary patterns. Anthropometric data on weight and height was collected to determine nutritional status using WHO Anthroplus 2010 software. A multivariable binary logistic regression model was used to identify factors affecting the dietary patterns of adolescents. Result: Three types of dietary patterns, namely traditional, mixed, and animal-source foods with traditional alcoholic beverage consumption were identified. The burden of stunting was 15.12% vs. 11.21%, 19.40% vs. 6.94%, and 8.36% vs.17.97% among adolescents with lower traditional, mixed, and higher animal sources with alcoholic dietary pattern consumption habits, respectively (P-value < 0.05). Adolescents who resided in low-land agroecology (AOR = 2.44; 95% CL: 1.24, 4.81) and had access to animal-source foods (AOR = 1.64; 95% CI: 1.04, 2.60) were associated with lower consumption of traditional dietary patterns. Similarly, adolescents who resided in lowlands (AOR = 1.80; 95% CI: 1.18, 2.74), had formal education (AOR = 2.38; 95% CI: 1.35, 4.19), and had poor nutrition knowledge (AOR = 2.83; (95% CL: 1.55, 5.19) were associated with lower consumption of mixed dietary patterns. Moreover, adolescents residing in the highlands (AOR = 2.50; 95% CI: 1.37, 4.56) and being female (AOR =1.87; 95% CI: 1.27, 2.74) were significant factors associated with lower consumption of animal-sourced foods with traditional alcoholic beverage consumption patterns. Conclusion: Multidimensional modifiable factors were explored, that could be targeted for public health interventions for the identified dietary patterns. Integrated and multifaceted dietary intervention approaches are needed to promote healthy diets and discourage the consumption of unhealthy diets to reduce undernutrition in the study area and similar settings.